(untitled) (Hackensack, N.J., 2004)
The book contains the text of lectures given at the third of a series of biennial symposia in mathematical physics held in odd-numbered years. The subject of the symposium is the frontiers of mathematical physics. It deals with quantum phenomena and includes topics such as string theory and quantum gravity, particle physics and field theory, non-communative geometry, integrable models and infinite dimensional symmetry groups, quantum computing and information processing, and quantum chaos.
Keywords: Symmetry (Physics),Quantum theory,Mathematical physics; Toán lý,Lý thuyết lượng tử